Interventions to Enhance Adherence to Oral Antineoplastic Agents: A Scoping Review. (5th January 2020) - Rosenberg, Shoshana M; Petrie, Keith J; Stanton, Annette L; Ngo, Lan; Finnerty, Emma; Partridge, Ann H
Abstract: Background: As new targeted oral antineoplastic therapies have emerged in recent years, the development of effective strategies that promote optimal adherence to cancer medication regimens has become an important priority. Methods: We conducted a scoping literature review to search for English language articles published through July 15, 2019, to identify studies that reported the testing and/or evaluation of interventions to improve adherence to oral antineoplastic agents. Results: A total of 56 articles were selected for review. Of the studies evaluated, 14 were randomized trials. All interventions except two targeted adult patients. Thirty-three studies enrolled fewer than 100 patients. Most interventions were education- and counseling-based and centered on provision of information about the drug and strategies to manage side effects. Only eight studies used an mHealth tool and/or text messages to target nonadherence. Among studies with a comparison sample, fewer than one-half (44.7%) reported statistically significant improvements in adherence or persistence associated with the intervention; however, some pharmacist-directed programs, particularly those that integrated monitoring or routine follow-up with a provider, did demonstrate efficacy. Conclusion: Although the development of adherence-promoting interventions for oral antineoplastic therapies has increased recently, few have been rigorously tested. The nascent literature suggests those that are pharmacist directed and use regular monitoring show promise, though additional prospective studies are needed. Study methodology, population selection, and potential challenges that may be encountered in the implementation and dissemination phases should be considered when developing new interventions to address nonadherence to oral antineoplastic treatment.